Experimentos de baixo custo para o ensino da física: uso do miriti como matéria prima - TORRES, Leonilson dos Santos (2024)
The present work aims to discuss the importance of working with low cost experiments in Physics classes, using Miriti as the regional raw material. This research is justified by the difficulty faced by students in teaching physics learning and that the use of experiments made from the raw material Regional Miriti can contribute to remedy or reduce these difficulties, as they enable the continuous development of teaching and teaching practices. learning with low-cost materials. For this, the general objective of this research is to develop low-cost experiments from miriti, aimed at demonstrating Physics content in the classroom. As a methodology, bibliographic research was used, with the objective of obtaining some information on the theme addressed here, thus being able to go deeper into the research starting from what theorists such as Preussler et al. (2017), Pereira et al. (2016), Souza (2014) and the official documents of Physics teaching. As a result, the research contributed to reflection on the use of Miriti as an alternative of low-cost material for demonstration experiments in physics classes, with Miriti being a viable alternative for the appropriation of concepts and knowledge that contribute to the improvement of the pedagogical practice of teacher translating into meaningful learning for the student regarding the contents of Physics.